2012
DOI: 10.1021/ed300008c
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Quantitation of FD&C Red Dye #40 from Beverages Containing Cranberry Juice: A College-Level Analytical Chemistry Experiment

Abstract: A chemical separation experiment can be an interesting addition to an introductory analytical chemistry laboratory course. We have developed an experiment to extract FD&C Red Dye #40 from beverages containing cranberry juice. After extraction, the dye is quantified using colorimetry. The experiment gives students hands-on experience in using solid phase extraction to extract the red dye from other colorants in the red beverages. Students are also given experience with colorimetry, the Beer−Lambert law, and som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…[ 14 ] In the commercially available preparations of cranberry juice, apart from the naturally available anthocyanin pigment in the cranberries, red azo dyes are used to impart the red color to the drink. [ 15 ] These dyes are water soluble and this property is a prerequisite for their excretion in the eccrine sweat. [ 5 10 ] Hence, the reddish discoloration of sweat in our case may be due to the excretion of the unchanged dye (anthocyanin and azo dye) present in the juice into the eccrine glands.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] In the commercially available preparations of cranberry juice, apart from the naturally available anthocyanin pigment in the cranberries, red azo dyes are used to impart the red color to the drink. [ 15 ] These dyes are water soluble and this property is a prerequisite for their excretion in the eccrine sweat. [ 5 10 ] Hence, the reddish discoloration of sweat in our case may be due to the excretion of the unchanged dye (anthocyanin and azo dye) present in the juice into the eccrine glands.…”
Section: Discussionmentioning
confidence: 99%
“…Many articles can be found that describe analogies, simulations, and activities to assist students in understanding the concept of equilibrium, and others report on common misconceptions and how to address them. Analytical applications in which the direct consideration of equilibria is either more complicated or perhaps less immediately apparent to students are presented by topics such as sample preparation using solid phase extraction or how acid–base or EDTA indicator solutions work. ,− Additionally, the dependence of retention of weak acids and bases on pH in HPLC also presents opportunities for connecting equilibria learned in multiple courses to the practice of analytical chemistry. , Often the concept of competing equilibria is introduced when discussing buffer solutions, and specifically buffer capacity, where the acid and conjugate base equilibria compete to maintain the pH upon addition of a strong acid or base to the system.…”
Section: Introductionmentioning
confidence: 99%
“…Discoveries about antioxidant properties of certain foods have led to investigations to understand how polyphenols, anthocyanins, and related compounds contribute to antioxidant properties and to potential health benefits. Two recent studies documented a decreased risk of myocardial infarction and arterial stiffness in women with a consistent intake of foods high in anthocyanins. , Anthocyanins have been used to develop laboratory experiments and outreach activities and are included in an effort to use natural products to teach chemical analysis . The experiments described herein teach students the techniques of solid–liquid extraction, reflux, paper chromatography, UV–vis spectroscopy, and radical scavenging assays within the context of natural products they frequently ingest.…”
Section: Introductionmentioning
confidence: 99%